Creative Writing in the Digital World: Assessing the Impacts of Digital Media on the Creative Writing Skills of Undergraduate Students - Dr. Tariq; Sayed Muhammad Abbas; Uzma Begum; Zaheer Ullah; Salman Abdullah (Review Journal of Social Psychology & Social Works, 2025)
This study investigates the influence of digital media on the creative writing skills of undergraduate students at the University of Malakand, utilizing the Atkinson and Shiffrin Model of Information Processing (1968) as a theoretical framework. Employing a mixed-method approach, data were collected from 100 students through questionnaires and from 15 students through interviews. Quantitative data were analyzed using statistical methods to identify patterns and relationships between digital media use and creative writing skills, while qualitative data provided insights into students’ attitudes and experiences. The findings reveal a complex relationship wherein digital media can enhance creativity by facilitating idea generation and engagement with diverse content, yet simultaneously present challenges for some students in maintaining focus and writing with depth. Notably, students who managed to balance digital media use with traditional writing practices exhibited superior performance in creative writing. These results suggest that integrating digital media literacy into the curriculum can foster both creative and critical thinking skills. Furthermore, this study contributes to the understanding of the Atkinson and Shiffrin Model by elucidating the influence of digital media on cognitive processes involved in creative writing. The study acknowledges limitations, including sample size and generalizability, and recommends that future research should explore the long-term effects and effective strategies for incorporating digital media in education. In conclusion, this research advances our comprehension of the impact of digital media on creative writing skills and offers practical recommendations for educators and policymakers, while also underscoring the necessity for continued research in the intersection of digital media and creativity.